Changes Over Time in Nasopharyngeal Colonization in Children Under 2 Years of Age at the Time of Diagnosis of Acute Otitis Media (1999–2014). (17th February 2018) - Martin, Judith M; Hoberman, Alejandro; Shaikh, Nader; Shope, Timothy; onika Bhatnagar, S; Block, Stan L; Haralam, Mary Ann; Kurs-Lasky, Marcia; Green, Michael
Abstract: Background: In children with acute otitis media (AOM), a decrease in nasopharyngeal (NP) colonization with vaccine serotypes of Streptococcus pneumoniae has been noted since the introduction of pneumococcal conjugate vaccines (PCVs). The purpose of this study is to describe corresponding changes in colonization with Haemophilus influenzae. Methods: In 4 separate studies, we obtained NP cultures from children aged 6–23 months presenting with AOM. Cohort 1 was recruited before routine use of PCV7 (1999–2000); 93% of children in cohort 2 (2003–2005) and 100% in cohort 3 (2006–2009) received ≥2 doses of PCV7. All children in cohort 4 (2012–2014) received ≥2 doses of PCV13. Isolates of H. influenzae were tested for ß-lactamase production; ß-lactamase negative isolates from cohorts 3 and 4 underwent susceptibility testing. Results: A total of 899 children were evaluated. NP colonization with H. influenzae was found in 26% of children in cohort 1 (n = 175), 41% in cohort 2 (n = 87), 33% in cohort 3 (n = 282), and 29% in cohort 4 (n = 355). Colonization with H. influenzae increased initially from cohort 1 to cohort 2 ( P = .01), then decreased across cohorts 2, 3, and 4 ( P = .03, test for trend). The prevalence rates of ß-lactamase production were 27%, 42%, 33%, and 30% in each of the 4 cohorts, respectively ( P = .50). Conclusions: Although an initial increase in H. influenzae colonization was observed, suggesting an impact of PCVs, the most recent prevalence rates of NP colonization with H. influenzae and ß-lactamase production were like those observed before universal administration of PCV7. This knowledge is critical to guide appropriate treatment recommendations for children with AOM.